Fattening heifer calves on dry bluestem pasture versus fattening in drylot - Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Heifers used in this experiment were the light end of calves purchased from the Pumray Ranch, Logan, N.M., the fall of 1957. Twenty-one heifers were placed in two groups on the basis of live weight and grade. One lot of 10 heifers, averaging 346 pounds each, was placed on 18 acres of dry mature bluestem pasture. The second lot of 11 heifers was put in drylot.
Keywords: Beef; Heifer; Bluestem pasture; Drylot